El piojo harinoso (Phenacoccus sp.) de la yuca; una de las plagas agricolas mas importantes en el mundo - Bellotti, Anthony C.; Reyes, J.A.; Varela, Ana M.; Castillo, J. (International Center for Tropical Agriculture, 1983)
Cassava mealybugs constitute one of the major production problems of cassava in Africa and the Americas. The species already identified that attack cassava in the Americas include Phenacoccus manihoti, P. herreni, P. gossypii, and P. grenadensis. Since its introduction into Africa, P. manihoti has caused considerable yield losses in some regions, especially Zaire. In the Americas, severe outbreaks of P. herreni have been reported in several areas of Brazil, Colombia, and the Guianas. These 2 species are similar taxonomically and in plant damage symptoms but differ biologically. The initial and most severe attack of both species occurs on the growing point of the cassava plant shoots. Plant reaction consists of a rosetting effect on the apical leaves which results in a cabbage-like appearance of the shoot. High mealybug populations, together with the stress caused by drought, cause defoliation, deformation of the shoots, shortening of internodes, and distortion of stems. The bionomics of both species differ in that P. herreni is bisexual and P. manihoti reproduces parthenogenetically. Biological studies on P. herreni show that the female passesthrough 3 instars before the adult stage. The complete life cycle from egg to adult lasts 49.5 days. Males pass through 4 instars before the adult stage, in which the adult male is winged. The whole cycle lasts 29.5 days. The cassava mealybug has numerous natural enemies. Biological control combined with resistance offers a healthy and economical control of the pest. Tables are included on the life cycle of P. herreni and P. gossypii on plants of cassava var. M Col 113 under lab. conditions, size and size increase of P. herreni on cassava under greenhouse conditions, hyperparasites of Phenacoccus spp. in Latin America, populations of natural enemies of the cassava mealybug in the field, and natural enemies of P. gossypii and P. herreni in Latin America and the Caribbean. (AS)